Contextual-Based Learning Video Media for Mathematics Content on Multiplication for Grade V Elementary School Students - Ni Putu Anjani Dyah Pramesti; I Wayan Wiarta; Dewi Anzelina (Mimbar Ilmu, 2026)
The low learning outcomes of elementary school students in mathematics, particularly in abstract topics such as fraction multiplication, are caused by the limited availability of learning media that can connect mathematical concepts with students’ real-life experiences. This study aims to analyze the feasibility, practicality, and effectiveness of developing a contextual-based learning video media to improve students’ mathematics learning outcomes. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants of this study were fifth-grade elementary school students. Data were collected using expert validation sheets, student response questionnaires, and learning achievement tests. The data were analyzed using descriptive qualitative and quantitative methods. The results show that the developed learning media is highly feasible based on expert evaluations in the aspects of instructional design, media quality, and content accuracy. In addition, the media is considered practical based on positive student responses during individual and small group trials. Furthermore, the learning media is proven effective in improving students’ mathematics learning outcomes. Therefore, it can be concluded that the contextual-based learning video is feasible, practical, and effective for use in mathematics instruction. The implication of this study is that teachers are encouraged to integrate contextual and digital learning media to create more interactive, meaningful, and student-centered learning experiences aligned with 21st-century education demands.